Current Topics in Pharmacological Research on Bone Metabolism: Inhibitory Effects of Bisphosphonates on the Differentiation and Activity of Osteoclasts - Keiko Suzuki; Sadaaki Takeyama; Yasushi Sakai; Shoji Yamada; Hisashi Shinoda (Elsevier, 2006)
Abstract.: Despite the extensive use of bisphosphonates (BPs) in the treatment of metabolic bone diseases associated with increased osteoclastic bone resorption, the precise mechanism of their action on bone metabolism is still unclear. To clarify at which stages of osteoclast differentiation and activation that BPs influence, we examined the osteoclasts generated from mononuclear precursors and osteoclasts in the calvaria by laser scanning confocal microscopy. The studies showed that BPs inhibit lipopolysaccharide- or parathyroid hormone-induced osteoclast differentiation, fusion, attachment, actin ring formation, and activation and that both β3 integrin and osteopontin have an important role in cytoskeletal rearrangements associated with cell attachment and resorption in osteoclasts. Keywords:: bisphosphonate, osteoclast, calvaria, confocal microscopy, osteopontin